2011
DOI: 10.1128/iai.05661-11
|View full text |Cite
|
Sign up to set email alerts
|

Retracted Science and the Retraction Index

Abstract: Articles may be retracted when their findings are no longer considered trustworthy due to scientific misconduct or error, they plagiarize previously published work, or they are found to violate ethical guidelines. Using a novel measure that we call the “retraction index,” we found that the frequency of retraction varies among journals and shows a strong correlation with the journal impact factor. Although retractions are relatively rare, the retraction process is essential for correcting the literature and mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
195
3
13

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 303 publications
(229 citation statements)
references
References 90 publications
6
195
3
13
Order By: Relevance
“…3D). An association between impact factor and retraction for fraud or error has been noted previously (4,6,29,30). This finding may reflect the greater scrutiny accorded to articles in high-impact journals and the greater uncertainty associated with cutting-edge research.…”
Section: Discussionmentioning
confidence: 62%
“…3D). An association between impact factor and retraction for fraud or error has been noted previously (4,6,29,30). This finding may reflect the greater scrutiny accorded to articles in high-impact journals and the greater uncertainty associated with cutting-edge research.…”
Section: Discussionmentioning
confidence: 62%
“…Alternatively, the variable prevalence of duplication could be partly accounted for by variations in the average number of figures and the number of panels per figure, which is likely to differ per journal but was not determined in our study. The inverse correlation between the prevalence of problematic papers and journal impact factor contrasts with the positive correlation observed for research misconduct resulting in retraction (8,(21)(22)(23). Although the association was weak, it may suggest that higher impact journals are better able to detect anomalous images prior to publication.…”
Section: Discussionmentioning
confidence: 61%
“…Reviewers often fail to detect major methodological failings ( Schroter et al , 2004), with eminent journals (whose higher rejection rates might suggest more stringent peer review processes) seeming to perform no better than others ( Fang et al , 2012). Indeed, Fang and Casadevall found that the frequency of retraction is strongly correlated with the journal impact factor ( Fang & Casadevall, 2011). Whatever the cause, recent sharp rises in the number of retracted scientific publications ( Steen et al , 2013) testify that peer review sometimes fails in its role as the gatekeeper of science, allowing errors to enter the literature.…”
Section: Introductionmentioning
confidence: 99%